Pengaruh Implementasi Sistem Pengendalian Internal Pemerintah, Implementasi Standar Akuntansi Pemerintah, Dan Implementasi Manajemen Resiko Terhadap Kualitas Laporan Keuangan - Pertiwi, Tiara Trias; Hariyanti, Dwi; Basuki, Ferry Hendro (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to find out empirically about the Implementation of the Government Internal Identification System (SPIP), the Implementation of government accounting standards (SAP), and the Implementation of Risk Management on the Quality of the Ambon City government's Financial Reports. The variables used in this research are the Implementation of the Government Internal Control System (SPIP), the Implementation of government accounting standards (SAP), and the Implementation of Risk Management as independent variables, as well as the quality of financial reports as the dependent variable. The method used to analyze the data is multiple regression statistical analysis. The sample in this study was 74 people consisting of Heads, Secretaries and Heads of Agency and Service divisions. The research results state that the Implementation of the Government Internal Control System/SPIP (X1) has a positive and significant effect on the Quality of Financial Reports (Y) of 0.139 or 13.9%, Implementation of Government Accounting Standards/SAP (X2) has a positive and significant effect on the Quality Financial Reports (Y) amounted to 0.159 or 15.9%, Implementation of Risk Management/MRES (X3) had a positive and significant effect on the quality of Financial Reports (Y) amounted to 0.357 or 35.7%.